First strike: educational enclosures in Black Los Angeles - Sojoyner, Damien M. (University of Minnesota Press, 2016)
Introduction : the problematic history between schools and prisons -- The problem of Black genius : Black cultural enclosures -- In the belly of the beast : ideological expansion -- Land of smoke and mirrors : the meaning of punishment and control -- Troubled man : limitations of the masculinity solution -- By all means possible : the historical struggle over Black education -- Conclusion : reading the past and listening to the present